EV A 99 reduced : Exhibition of Visual Art 1999. - Greenberg Rohatyn, Jeanne; Murray, Hugh; O'Reilly, Paul M.; Exhibition of Visual+Art Limerick 1999; Limerick City Gallery of Art (Limerick : Limerick City Gallery of Art, 1999)
ADF ; Behan, Geraldine ; Burrell, Lorraine ; Byrne, Fergus ; Byrne, Gerard ; Canning, Michael ; Carters, Colin ; Cleary, Carmel ; Colman, Eamon ; Comerford, Oliver ; Connolly, Maeve ; Coogan, Amanda ; Copperwhite, Diana ; Corcoran, Margaret ; Derbyshire, Beth ; Doyle, Jeanette ; Duffy, Joyce ; Duffy, Rita ; Duggan, Frances ; Dunsmore, Amanda ; Durcan, Sarah ; Earley, Brendan ; Farrell, Carissa ; Fortune, Michael ; Gorey, Helena ; Harahan, Seamus ; Healy, Martin ; Hogan, Darragh ; Holten, Katie ; Hughes, Ronnie ; Janz, Bob ; Jewesbury, Daniel ; Kelly, Aileen ; Kelly, Mary ; Lambert, Aileen ; Loughman, Stephen ; MacWilliam, Susan ; Martin, Fergus ; McAllister, Terry ; McAuliffe, Diarmuid ; McCarthy, Eoin ; McGrath, Dara ; McQuinn, Austin ; Meehan, Sandra ; Molntyre, Mary ; Morgan, Peter ; Mulholland, Fiona ; Nic Giolla Coda, Aine ; O'Brien, Abigail ; O'Connor, Maureen ; O'Kane, Eamon ; O'Leary, Helen ; O'Mahony, Deirdre ; O'Malley, Niamh ; O'Mara, David ; O'Neill, Paul ; O'Rourke, Seamus ; Orange, Mark ; Rooney, Declan ; Ryan, Bernie ; Savage, Jim ; Taylor, Sean
biog., tent., performances, coll., prijzen p. 129-149
Engels
EV+A 99 reduced : Exhibition of Visual Art 1999, Limerick City Gallery of Art Limerick, 22 May - 17 July 1999
boek